Photophysical properties of two novel tetraphenylporphyrins substituted by guanidiniocarbonyl and monocyclic guanidine groups - Pavel Kubát; Kamil Lang; Vladimír Král; Franz P. Schmidtchen (International Journal of Photoenergy)
Photophysical properties of two novel guanidiniocarbonyl (I) and monocyclic guanidine (II) tetraphenylporphyrins and their interaction with DNA were investigated by steady-state and time-resolved absorption and emission spectroscopies. I stays predominantly monomeric in aqueous solutions. It produces singlet oxygen with high quantum yield (ΦΔ=0.67) that is typical for monomeric porphyrins. The electronic absorption spectra of I are not influenced by interaction with DNA. This is in contrast with monomeric tetratolylporphyrins bearing phosphonium,ammonium and pyridinium groups where the formation of stable complexes with DNA is accompanied by a characteristic red shift of the Soret band. II extensively forms Hand J-aggregates,which do not produce singlet oxygen (ΦΔ<0.01). In the presence of DNA only a small fraction of II remains in monomeric form that is bound to DNA exterior.